Introduction to Computational Thinking at SD Muhammadiyah 1 Jember Through Game Making Training Among Us: Pengenalan Computational Thinking Di SD Muhammadiyah 1 Jember Melalui Pelatihan Pembuatan Game Among Us - Ilanka Cahya Dewi; Ridho Ananta Bahariawan; Ari Setyo Gumilang; Sukma Nurul Aini; Noeril Agian Septa Dinata; Yeni Dwi Rahayu (Yayasan Ahmar Cendekia Indonesia, 2022)
Computational thinking is one of the problem solving strategies that can be used widely and unlimited by the field of computer science but also everyday problems. This method stimulates to think in a structured and systematic way as well as when software developers analyze requirements and design software development. SD Muhammadiyah 1 (SDMutu) Jember is an elementary school that pays great attention to the development of the quality and quality of education in it. SDMutu is a reference and education center for Muhammadiyah elementary schools in Jember district. Various development breakthroughs have been made, one of which is related to the adoption of computational thinking. SDMutu has an adequate computer laboratory but still needs partners in order to strengthen its adaptive strategy. The training is given directly to some selected students, and involves the teacher as an observer so that the teacher has input for the next development. The experience of students participating in the training is also a very influential part of the observation. The training is provided through 5 material sessions using the Scratch programming language so that students can understand it well. At the beginning of the training, students seemed enthusiastic and happy, this atmosphere was built so that students could participate in the training to the fullest. Based on the post-test results, the average student understanding is 5.6 with a range of 0-10. During the making of the game the students stably followed the step by step until it was finished. So that at the end of the post-test activity the students showed an increase to 7.6. Abstrak Computational thinking atau yang disebut juga dengan berpikir komputasi merupakan salah satu strategi penyelesaian masalah yang dapat digunakan secara luas dan tidak terbatas pada bidang ilmu komputer saja tetapi juga permasalahan sehari-hari. Metode ini mengajak untuk berpikir secara terstruktur dan sistematis sama halnya ketika pengembang perangkat lunak menganalisis kebutuhan dan merancang pengembangan software. SD Muhammadiyah 1 (SDMutu) Jember merupakan sekolah dasar yang sangat memperhatikan pengembangan mutu dan kualitas pendidikan didalamnya. SDMutu merupakan rujukan dan kiblat pendidikan sekolah dasar Muhammadiyah di kabupaten Jember. Berbagai terobosan pengembangan telah dilakukan salah satunya terkait adopsi computational thinking. SDMutu memiliki Laboratorium komputer yang memadai namun masih membutuhkan mitra agar dapat memperkuat strategi adaptif. Pelatihan diberikan langsung kepada sebagian siswa terpilih, dan melibatkan guru sebagai observer agar guru memiliki masukan untuk pengembangan berikutnya. Pengalaman siswa yang mengikuti pelatihan juga merupakan bagian obeservasi yang sangat berpengaruh. Pelatihan diberikan melalui 5 sesi materi menggunakan Bahasa pemrograman scratch agar siswa dapat memahami dengan baik. Diawal pelaksanaan pelatihan siswa nampak antusias dan senang, suasana ini dibangun agar siswa dapat mengikuti pelatihan dengan maksimal. Berdasarkan hasil post-test rata-rata pemahaman siswa ada di angka 5,6 dengan range 0-10. Selama pembuatan game siswa secara stabil mengikuti tahapan demi tahapan hingga selesai. Sehingga diakhir kegiatan post-test siswa menunjukkan peningkatan menjadi 7.6.